2014
DOI: 10.1016/j.jpha.2013.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Stability-indicating HPLC–DAD methods for determination of two binary mixtures: Rabeprazole sodium–mosapride citrate and rabeprazole sodium–itopride hydrochloride

Abstract: Two selective stability-indicating HPLC methods are described for determination of rabeprazole sodium (RZ)–mosapride citrate (MR) and RZ–itopride hydrochloride (IO) mixtures in the presence of their ICH-stress formed degradation products. Separations were achieved on X-Bridge C18 column using two mobile phases: the first for RZ–MR mixture consisted of acetonitrile: 0.025 M KH2PO4 solution: TEA (30:69:1 v/v; pH 7.0); the second for RZ–IO mixture was at ratio of 25:74:1 (v/v; pH 9.25). The detection wavelength w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…Stability study of RZL and ACF demonstrated satisfactory results. The type of degraded product formed, R f value and the percent drug recovery variation showed the differences from the results reported in literature for drug degradation by other analytical methods [17,[19][20] because of the nature, methodology and extent of degradation. The study activity was limited till the formation of chromatogram of degraded drug sample, its approximate interpretation, nevertheless there is a scope for the separation, quantification and analysis of the degraded products.…”
Section: Discussion and Overall Conclusioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Stability study of RZL and ACF demonstrated satisfactory results. The type of degraded product formed, R f value and the percent drug recovery variation showed the differences from the results reported in literature for drug degradation by other analytical methods [17,[19][20] because of the nature, methodology and extent of degradation. The study activity was limited till the formation of chromatogram of degraded drug sample, its approximate interpretation, nevertheless there is a scope for the separation, quantification and analysis of the degraded products.…”
Section: Discussion and Overall Conclusioncontrasting
confidence: 74%
“…Although, various analytical techniques has been developed for estimation of RZL and ACF individually or with other components in bulk drug and pharmaceutical dosage forms, the most suitable, efficient and cost effective HPTLC method has not yet been determined [15][16][17][18][19][20][21][22][23] Similarly, this technique has not been used for stability indication of drugs so far. It requires modification depending on the factors that predict the better resolution, validation within accepted limits and clear separation from degradation products.…”
Section: Introductionmentioning
confidence: 99%
“…Literature survey reveals that there are methods to analyse these drugs by spectroscopic methods [3][4], in tablet [5][6][7][8][9][10][11][12][13][14][15][16], in plasma [17][18].There are no methods reported in tablets using Buffer and Acetonitrile as solvent which is cost effective.…”
Section: Introductionmentioning
confidence: 99%
“…It speeds gastrointestinal peristalsis, causes prolactin release, and is used as antiemetic and tool in the study of dopaminergic mechanisms. Lansoprazole chemically is 2-({[3-methyl-4-(2, 2, 2-trifluoroethoxy) pyridin-2-yl] methane} sulfinyl)-1H-1, 3-benzodiazole and used as a proton pump inhibitor which prevents the stomach from producing acid [1-2].Literature survey reveals that there are methods to analyse these drugs by spectroscopic methods [3][4], in tablet [5][6][7][8][9][10][11][12][13][14][15][16], in plasma [17][18].There are no methods reported in tablets using Buffer and Acetonitrile as solvent which is cost effective.Hence an attempt is made to develop simple, Accurate and Precise and cost effective method [19][20] for simultaneous estimation of Lansoprazole and Domperidone by RP-HPLC in tablet dosage form according to ICH guidelines [21].…”
mentioning
confidence: 99%